Electrochemical modification of carbon nanotube fibres. Issue 26 (17th May 2022) - Dominguez-Alfaro, Antonio; Chau, Ngoc Do Quyen; Yan, Stephen; Mancino, Donato; Pamulapati, Sushma; Williams, Steven; Taylor, Lauren W.; Dewey, Oliver S.; Pasquali, Matteo; Prato, Maurizio; Bianco, Alberto; Criado, Alejandro
Abstract : Versatile, simple, fast and non-damaging electrochemical modification of carbon nanotube fibres. Abstract : Covalent modification of the surface of carbon nanotube fibres (CNTFs) through electrochemical reduction of para -substituted phenyldiazonium salts and electrochemical oxidation of an aliphatic diamine is described. Following these strategies, diverse surface functionalities have been introduced while preserving the fibre bulk properties. The corresponding modified CNTFs were fully characterised by Raman spectroscopy, X-ray photoelectron spectroscopy, energy dispersive X-Ray, scanning electron microscopy and electrochemical impedance spectroscopy, exhibiting different surface properties from those of the unmodified CNTFs.